HUBUNGAN KECEPATAN DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA PUTRA KELAS VIII A SMP METHODIST PEKANBARU - Merry Frezy Br S; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on the observation of authors in carrying out observations in a male student of class VIII at the Pekanbaru Methodist Middle School, the data description of this research consisted of two variables, namely variables, namely free speed (X) and dependent variable as a result. of the offset (Y). Speed measurement was performed with 30 meters run against 15 samples, the best results achieved 3.45, worst results 5.94, mean (average) 4.93, standard deviation (standard deviation) 0.83, based on the frequency distribution table of the 8 samples showed that there were 2 samples (13.33%) with the results of velocities with a range of values from 3.45 to 3.94 with excellent categories, then 2 samples (13.33%) had a velocity with a range of values 3.95-4.44 with good categories, and 2 samples (13.33%) had the results of speed with a range of values from 4.45 to 4.94 with moderate categories, then had 4 people in the sample (26.66%) results speed with a range of values from 4.95 to 5.44 with fewer categories and 5 samples (33.33%) to have a velocity with a range of values of 5.45 -5.94 with a category of very little. The measurement of the results of the long jump was performed using the offset test for 15 samples, the best result was 2.60, the worst result was 3.83, the average (mean) was 3.30, the standard deviation was 0, 41. The first test is that there is a correlation between speed and the results of the long jump. From the information above obtained a correlation analysis between speed and the results of the long jump, where the rtab at a significant level (0.05) = 0.0.514 means r count (1.452)> rtab (0.514) then there is a significant correlation.Keywords : speed, long jump